Code of ethics - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The present code of ethics respects the rules of the Institute contained in the regulations of the General Directorate, Personnel and Financial. This code aims to: a) ensure the human dignity and well-being of the officials of the Institute; b) build ethics based on the recognition of the value of the person in his great diversity; c) promote coexistence in an environment based on principles of high moral solvency, so that officials can perform to the maximum extent in all their capacities and dimensions